PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS MODEL PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN KREATIVITASSISWA KELAS IV SD 10 KOTO BARU PADA TEMA 6 SUBTEMA 1 - SUPARYANTI, RATNAWATI ARWIN (Inovasi Pendidikan, 2017)
One problem that happen in learning especially theme 6 and sub-theme 1 (theme what a beautiful my country and sub-theme the varieties of animals and plants) are the limitedness of students’ worksheet (LKS). At present, the available of students’ worksheet do not meet the requirement and do not based on the criteria in thematic learning model, yet. In addition, it cannot activate the students in the learning process. The purpose of this study is to produce the students’ worksheet in which valid based on thematic learning, what a beautiful my country and sub-theme the varieties of animals and plants in grade IV SD Koto Baru, Dharmasraya. This students’ worksheet is hoped to improve the students’ creativity and learning outcomes.The design of this study was design-based research, in Indonesia; it is named Research and Development. The design used in this study by following the process that developed by Sugiyono in which it consists of 10 phases; 1) the identification of the problem, 2) the collecting of information, 3) product design, 4) design validity, 5) design revision, 6) examination of product, 7) product revision, 8) test the product usage, 9) last revision of product, 10) production. The development of students’ worksheet in this study only uses 5 procedures. The validity of students’ worksheet is examined by 3 experts.The results of the development showed that the theme what a beautiful my country and sub-theme the varieties of animals and plants based on thematic learning in students’ worksheet at grade IV SDN Koto Baru, Dharmasraya were valid with scores 72%. It is based on the contents, constructions (the component of presentations), and the language used for learning at the 2nd semester grade IV SD. Based on the results above-showed, then the students’ worksheet can be examined.Keyword: Development, Students’ Worksheet, Thematic